Customer satisfaction and sustainability initiatives in the fourth industrial revolution - Silvestri, Cecilia, 1982-; Piccarozzi, Michela, 1982-; Aquilani, Barbara, 1969- (Advances in marketing, customer relationship management, and e-services (AMCRMES) book series., 2020)
"This book links together three highly relevant topics in the business of modern economy-innovation, customer satisfaction, and sustainability-and analyzes their synergies"--Provided by publisher.